Social cost-benefit analysis of hydrogen mobility in Europe. (9th November 2016) - Cantuarias-Villessuzanne, Carmen; Weinberger, Benno; Roses, Leonardo; Vignes, Alexis; Brignon, Jean-Marc
Abstract: The deployment of hydrogen technologies in the energy mix and the use of hydrogen fuel cell vehicles (FCV) are expected to significantly reduce European greenhouse emissions. We carry out a social cost-benefit analysis to estimate the period of socio-economic conversion, period for which the replacement of gasoline internal combustion engine vehicles (ICEV) by FCV becomes socio-economically profitable. In this study, we considered a hydrogen production mix of five technologies: natural gas reforming processes with or without carbon capture and storage, electrolysis, biogas processes and on-site production. We estimate two external costs: the abatement cost of CO 2 through FCV and the use of non-renewable resources in the manufacture of fuel cells by measuring platinum depletion. We forecast that carbon market could finance approximately 10% of the deployment cost of hydrogen-based transport and that an early economic conversion could be targeted for FCV. Almost ten years could be saved by considering externalities. Highlights: Including social costs could foster transition to hydrogen-based transport in Europe. Abatement cost of CO2 could finance about 10% of the deployment cost. Platinum depletion is almost as significant as the abatement cost of CO2 . Considering externalities could speed up the transition by 10 years.